Problems of Teaching Foreign Language Professional Guidanct for Students of Non-Linguistic Tehnical Specialities - Shevchuk, Tetiana R. (Міжнародний центр наукових досліджень, 2025)
The study of foreign languages has been and remains for many years an actual and problematic issue for students of technical specialties. The factors that led to gaps in theoretical and practical knowledge of the language are the insufficient level of language training at the previous educational stages, the lack of motivation for learning the language and learning in general, the wrongly selected approach to the student and the learning process is not effective, leading to the disappointment of students in the future language learning and other factors and problems. When studying a language at a technical higher education institution, the question of teaching the language in a professional direction becomes relevant, since a participant in the educational process must be a professional in his field and it is appropriate to master language skills and skills that would make him a specialist of the highest level. But, paying attention to the existing problems in teaching a foreign language for everyday use, we can say that teaching a professional language will also be complicated.